Preparation and Cytotoxic Evaluation of PGV-1 Derivative, CCA-1.1, as a New Curcumin Analog with Improved-Physicochemical and Pharmacological Properties - Rohmad Yudi Utomo; Febri Wulandari; Dhania Novitasari; Beni Lestari; Ratna Asmah Susidarti; Riris Istighfari Jenie; Jun-ya Kato; Sardjiman Sardjiman; Edy Meiyanto (Tabriz University of Medical Sciences, 2022)
Purpose: This study aimed to challenge the anticancer potency of pentagamavunone-1 (PGV-1) and obtain a new compound (Chemoprevention-Curcumin Analog 1.1, CCA-1.1) withimproved chemical and pharmacological properties.Methods: CCA-1.1 was prepared by changing the ketone group of PGV-1 into a hydroxylgroup with NaBH4 as the reducing agent. The product was purified under preparative layerchromatography and confirmed with HPLC to show about 93% purity. It was tested for itssolubility, stability, and cytotoxic activities on several cancer cells. The structure of the productwas characterized using 1HNMR, 13C-NMR, FT-IR, and HR-mass spectroscopy.Results: Molecular docking analysis showed that CCA-1.1 performed similar or better interactionto NF-κB pathway-related signaling proteins (HER2, EGFR, IKK, ER-alpha, and ER-beta) andreactive oxygen species (ROS) metabolic enzymes (NQO1, NQO2, GSTP1, AKC1R1, andGLO1) compared with PGV-1, indicating that CCA-1.1 exhibits the same or better anticanceractivity than PGV-1. CCA-1.1 also showed better solubility and stability than PGV-1 in aqueoussolution at pH 1.0-7.4 under light exposure at room temperature. The cytotoxic activities ofCCA-1.1 against several (10) cancer cell lines revealed the same or better potency than PGV-1.Conclusion: In conclusion, CCA-1.1 performs better chemical and anticancer properties thanPGV-1 and shows promise as an anticancer agent with high selectivity.